Targeted Dendrimer-Coated Magnetic Nanoparticles for Selective Delivery of Therapeutics in Living Cells - Paola Parlanti; Adriano Boni; Giovanni Signore; Melissa Santi (Molecules, 2020)
Nanoparticles are widely used as theranostic agents for the treatment of various pathologies, including cancer. Among all, dendrimers-based nanoparticles represent a valid approach for drugs delivery, thanks to their controllable size and surface properties. Indeed, dendrimers can be easily loaded with different payloads and functionalized with targeting agents. Moreover, they can be used in combination with other materials such as metal nanoparticles for combinatorial therapies. Here, we present the formulation of an innovative nanostructured hybrid system composed by a metallic core and a dendrimers-based coating that is able to deliver doxorubicin specifically to cancer cells through a targeting agent. Its dual nature allows us to transport nanoparticles to our site of interest through the magnetic field and specifically increase internalization by exploiting the T7 targeting peptide. Our system can release the drug in a controlled pH-dependent way, causing more than 50% of cell death in a pancreatic cancer cell line. Finally, we show how the system was internalized inside cancer cells, highlighting a peculiar disassembly of the nanostructure at the cell surface. Indeed, only the dendrimeric portion is internalized, while the metal core remains outside. Thanks to these features, our nanosystem can be exploited for a multistage magnetic vector.